Strategi Peningkatan Kualitas Rujak Kuah Pindang Di Warung D’Abian Kelan - Gita Kurniawati, Ni Kadek; Hartiati, Amna; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 12 No 3 (2024): SeptemberDO - 10.24843/JRMA.2024.v12.i03.p04, 2024)
ABSTRACT   Quality improvement in pindang sauce salad is the focus of research to get the right strategy as an effort to improve the process of making pindang sauce salad so that it can meet consumer satisfaction. Pindang sauce salad is a food that comes from a mixture of several fresh fruits using spices including fish broth and seasonings. The purpose of this study is to determine the quality attributes of products that are considered important to consumers of pindang sauce salad products, analyze the priority of improvement of pindang sauce salad products and determine the right strategy to improve the quality of pindang sauce salad products. The research method used is quality function deployment, using qualitative and quantitative data through observation and survey methods. The results obtained quality attributes that are considered important by consumers are the quality of pindang sauce, fruit quality, salad flavor, appearance, price, portion, durability, quality of shrimp paste. Prioritizing the improvement of the quality of pindang sauce salad in D'Abian Kelan shop is on the quality attribute of shrimp paste with the highest improvement ratio of (1.121), price attributes (1.119), and durability attributes (1.116). The strategy to improve the quality of pindang sauce salad at the D'Abian Kelan shop is to evaluate the technical parameters that have the highest priority for improvement based on the value of the level of technical importance, namely the technical parameters of raw material preparation, portioning of raw materials and making pindang sauce. Keywords : Pindang sauce salad, product quality, customer satisfaction, quality function deployment (QFD)   ABSTRAK   Peningkatan kualitas pada rujak kuah pindang menjadi fokus penelitian untuk mendapatkan strategi yang tepat sebagai usaha perbaikan proses pembuatan rujak kuah pindang sehingga dapat memenuhi kepuasan konsumen. Rujak kuah pindang merupakan makanan yang berasal dari campuran beberapa buah segar menggunakan bumbu diantaranya kaldu ikan dan bumbu penyedap. Tujuan penelitian ini yaitu mengetahui atribut mutu produk yang dianggap penting bagi konsumen produk rujak kuah pindang, menganalisis prioritas perbaikan terhadap produk rujak kuah pindang dan menentukan strategi yang tepat untuk meningkatkan kualitas produk rujak kuah pindang. Metode penelitian yang digunakan yaitu quality function deployment , menggunakan data kualitatif dan kuantitatif melalui metode observasi dan survei. Hasil penelitian didapatkan atribut mutu yang dianggap penting oleh konsumen yaitu kualitas kuah pindang, kualitas buah, rasa rujak, tampilan, harga, porsi, daya tahan, kualitas terasi. Prioritas perbaikan kualitas rujak kuah pindang di warung D’Abian Kelan yaitu pada atribut kualitas terasi dengan rasio perbaikan tertinggi sebesar (1.121), atribut harga (1.119), dan atribut daya tahan (1.116). Strategi untuk meningkatkan kualitas rujak kuah pindang di warung D’Abian Kelan adalah melakukan evaluasi terhadap parameter teknis yang memiliki prioritas perbaikan tertinggi berdasarkan nilai tingkat kepentingan teknis yaitu pada parameter teknis penyiapan bahan baku, pemorsian bahan baku dan pembuatan kuah pindang. Kata kunci : Rujak kuah pindang, kualitas produk, kepuasan konsumen, quality function deployment (QFD)